PENGARUH ELECTRONIC WORD OF MOUTH DAN PERSEPSI HARGA PRODUK LUAR NEGERI TERHADAP IMPULSIVE BUYING PENGGUNA E-COMMERCE SHOPEE (Studi Kasus Pada Generasi Z dan Milenial di Kota Depok) - Gerald Gorga; Yanita Ella Nilla Chandra; Husnil Barry; Riskon Ginting Ginting (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2022)
Shopping is one of the ways that people try to meet their needs. With the advancement of technology, the traditional method of shopping, which was originally a process in which consumers conducted trade interactions with producers face-to-face, has now begun to shift to using new modes of trade interaction, namely, using internet technology as a marketplace to develop all activity relationships between sellers and buyers. The study sought to ascertain the impact of electronic word of mouth and perception of foreign product prices on the impulse buying of Shopee E-Commerce users. Purposive sampling was used, with a total sample of 100 respondents from the city of Depok. A questionnaire was used to collect data in this study. PLS-SEM (Partial Least Squares-Structural Equation Modeling) with SmartPLS software was used to analyze the research data. With a coefficient value of 0.467 and a p-value of 0.000, the findings of this study indicate that Electronic Word of Mouth has an effect on Impulsive Buying. With a coefficient of 0.164 and a p-value of 0.095, price perception has an effect on Impulsive Buying.